Auditory Event-Related P300 Potentials in Rheumatoid Arthritis Patients - Tomasevic-Todorovic, S.; Boskovic, K.; Filipovic, D.; Milekic, B.; Grajic, M.; Hanna, F. (Нейрофизиология, 2015)
The aim of the study was to assess P300 event-related potentials (ERPs) in patients suffering from rheumatoid arthritis (RA) in relation to the duration of illness, degree of disease activity, anatomical and functional stage of the disease, pain intensity, and pain unpleasantness. The cross-sectional study included 53 women with RA (RA group; mean age 50.58 ± 0.93 years) and 27 healthy women (control group, C; 49.41 ± 1.08 years). The intensity and unpleasantness of pain were determined using a visual analog scale (VAS); the functional status was assessed using HAQ (Health Assessment Questionnaire), and the disease activity was estimated using the disease activity scale (DAS28). The P300 waves initiated by auditory stimulations according to the oddball paradigm were recorded from leads Fz and Cz. There were no significant differences between the P300 latencies in both leads. At the same time, the average P300 amplitudes in both leads were found to be considerably lower (P < 0.05) in the RA group compared to the C group. Thus, there is a statistically significant amplitude difference between the P300 cognitive ERPs in RA patients and control subjects. Були досліджені параметри пов’язаних із подією потенціалів (ППП) P300 у пацієнтів, що страждають на ревматоїдний артрит (РА), та зв’язок цих параметрів із тривалістю та інтенсивністю захворювання, анатомічною та функціональною стадіями останнього, інтенсивністю та неприємністю відчуттів болю. У порівняльне дослідження були залучені 53 жінки з РА (група RA, середній вік 50.58 ± ± 0.94 року) та 27 здорових жінок (контрольна група C, 49.41 ± 1.08 року). Інтенсивність та рівень неприємності болю визначали за допомогою візуальної аналогової шкали (VAS), функціональний статус – згідно з опитувальником HAQ, а інтенсивність хвороби – за шкалою DAS28. Потенціали P300 ініціювали акустичною стимуляцією відповідно до oddball-парадигми та відводили від точок Fz та Cz. Усереднені значення латентних періодів хвилі P300 в групах RA та C не демонстрували якихось істотних відмінностей. У той же час усереднені амплітуди P300 в обох кортикальних зонах у групі RA були вірогідно нижчими (P < 0.05), ніж відповідні величини в групі C. Таким чином, існує статистично значуща різниця між характеристиками когнітивного ППП P300 у пацієнтів із ревматоїдним артритом та здорових суб’єктів, що вказує на негативні зміни сенсорного процесінга та уваги, а також когнітивні дисфункції, виниклі під впливом хронічного болю.